Efektivitas Aplikasi TangselPay Dalam Perkembangan E-Governement di Kota Tangerang Selatan - Setyaningrum, Intan (Saraq Opat: Jurnal Administrasi Publik, 2023)
The South Tangerang City Government (Tangsel) is trying to make a new innovation in online-based public services, this is done because South Tangerang City is a city that carries the concept of 'Smart City'. TangselPay is one of the products that embodies the Smart City concept because it is a digital-based payment. The purpose of this research is to see how effective the TangselPay application is in the development of E-Government in South Tangerang City. The author sees that the existence of the Tangsel Smart City policy which gave birth to the TangselPay application can open the way between the Tangsel City government and the community. The research method is descriptive with a qualitative approach with data collection techniques through interviews, observations of the TangselPay application, and observations of related documents such as policies, system operational procedures and other obtained documentation. The results of the study show that there is still a lack of effectiveness in the TangselPay application, the main factor that the authors consider to be an obstacle is the very minimal socialization regarding the TangselPay application to the people of South Tangerang so that people who do not know about the existence of the TangselPay application from 2019 to 2022 dominate. This can be an evaluation of the South Tangerang City government so that it is optimal in realizing the Smart City concept as the development of E-Government in South Tangerang City.